2021
DOI: 10.1007/s42452-020-04031-z
|View full text |Cite
|
Sign up to set email alerts
|

Flow pattern and pressure drop for oil–water flows in and around 180° bends

Abstract: Pressure drop and flow pattern of oil–water flows were investigated in a 19-mm ID clear polyvinyl chloride pipe consisting of U-bend with radius of curvature of 100 mm. The range for oil and water superficial velocities tested was $$0.04 \le U_{{{\text{so}}}} \le 0.950 \;{\text{m/s}}$$ 0.04 ≤ U so ≤ 0.950 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…It was found that λ increases with increasing Re l , which is consistent with equation (5). Te main reason for this is that the increase in the fow rate increases the frictional shear between the fuid and the bend wall and the shear at the interface between the gas and liquid phases [25]. In addition, the secondary fow velocity at the bend also increases, increasing the local resistance.…”
Section: Efect Of Re L and α On The Local Resistancesupporting
confidence: 74%
“…It was found that λ increases with increasing Re l , which is consistent with equation (5). Te main reason for this is that the increase in the fow rate increases the frictional shear between the fuid and the bend wall and the shear at the interface between the gas and liquid phases [25]. In addition, the secondary fow velocity at the bend also increases, increasing the local resistance.…”
Section: Efect Of Re L and α On The Local Resistancesupporting
confidence: 74%